Comparative Analysis of DoS and DDoS Attacks in Internet of Things Environment - Aminu Ghali, A. (Springer, 2020)
With the high rate of accepting Internet of Things (IoT) from individual nowadays. The IoT devices comprises television sets (TV), voice controller, smart lock, smart light, speakers, nest smoke alarm, air conditioning, ring doorbell and smart plug etc. Thus, the impact of IoT provides many industries with new ways of handling business operations such as procurement, manufacturing, distribution of goods and service, etc. With the aid of intelligent sensors, actuators, etc., the industries have revolutionized to an era known as Industry 4.0 (IR4.0), where business operations can be done and potentially optimized, by controlling interconnecting âthingsâ via data communication channels. Similar to other electronic communication platforms in IoT ensuring security is paramount important especially in detecting the menace of the security challenges in the IoT environment. This paper aims to perform a comparative analysis between Denial of service (DoS) and Distributed denial of service (DDoS) attacks in the IoT environment. In essence, the comparative analysis reveals that the DDoS attack is the most significant attack to address in the IoT environment with about 68 Gbps requests compared to the DoS attack with 58 Gbps request. Â© 2020, Springer Nature Switzerland AG.